2020
DOI: 10.1017/rep.2019.51
|View full text |Cite
|
Sign up to set email alerts
|

Choosing Choice: How Gender and Religiosity Shape Abortion Attitudes among Latinos

Abstract: The relationship between religiosity and political attitudes is well established in the United States, particularly around gendered issues like abortion. However, this relationship can be complicated by the highly gendered and racialized nature of social identities. In this paper, we explore how different forms of religiosity (belonging to a denomination, specific religious beliefs, and religious behavior in church and in private) interact with gender to shape Latino abortion preferences. Using two sets of nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 80 publications
0
17
0
Order By: Relevance
“…Further, Bolks et al (2000) also found that Latinx attitudes toward abortion can be predicted by many of the same variables that predict non-Latinx abortion attitudes, including religiosity, feminist attitudes, income, age, and level of education. Other studies have corroborated the association among these variables, emphasizing, in particular, the importance of religious factors (e.g., denomination, beliefs, church attendance) in predicting Latinx abortion attitudes (e.g., Bartkowski et al, 2012;Ellison et al, 2005;Holman et al, 2020).…”
Section: Latinx Political Knowledge and Attitudes Toward Abortionmentioning
confidence: 85%
“…Further, Bolks et al (2000) also found that Latinx attitudes toward abortion can be predicted by many of the same variables that predict non-Latinx abortion attitudes, including religiosity, feminist attitudes, income, age, and level of education. Other studies have corroborated the association among these variables, emphasizing, in particular, the importance of religious factors (e.g., denomination, beliefs, church attendance) in predicting Latinx abortion attitudes (e.g., Bartkowski et al, 2012;Ellison et al, 2005;Holman et al, 2020).…”
Section: Latinx Political Knowledge and Attitudes Toward Abortionmentioning
confidence: 85%
“…This limits the generalizability of our findings to the broader population, and future research should explore the interaction between gender and race as it relates to sexism and political attitudes. For example, gender, race, and religiosity interact to shape abortion support, demonstrating the importance of these intersectional dynamics (Holman et al, 2020). More work needs to be done to fully understand the complexities of gender, race, and sexism in shaping political attitudes.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, an intersectional lens is necessary to fully understand the experiences and preferences of women, particularly of Black American women (Crenshaw, 1989;Hancock, 2007;Brown, 2014). Indeed, attitudes on reproductive rights in the U.S. differ across racial/ethnic groups as well as religious affiliations (Smith, 2013;Jelen, 2014;Lizotte, 2015;Holman et al, 2020). The rich body of literature on intersectionality is necessary to understand how sexism operates in society, but there is less work on empirically connecting measures of sexism to intersectionality (see Junn and Masuoka, 2020 for discussion on how variation in socioeconomic and religious indicators matter more for the white woman vote).…”
Section: The Impact Of Sexism On Policy Attitudesmentioning
confidence: 99%
“…Latinx as the other main contemporary immigrant community similarly possess important intragroup differences, including how they develop their sense of identity and feelings of ethnic linked fate (e.g. Vargas et al ., 2017; Maltby et al ., 2020), and form specific political attitudes like abortion (Holman et al ., 2020). It is important to acknowledge this heterogeneity within the historical construction of Asian American racial identity in contemporary politics in order to account for anti-Blackness among all Asian American (even ostensibly “conscious” Asian Americans).…”
Section: Asian Americans In An Anti-black Societymentioning
confidence: 99%